Het gebruik van geweld bij het bestraffen van overspel in Bijbelse teksten (Deuteronomium 22:13-29 en Johannes 7:53-8:11) - Weren, Wilhelmus Johannes Cornelis (HTS teologiese studies, 2008)
The use of violence in punishing adultery in Biblical texts (Deuteronomy 22:13-29 and John 7:53-8:11) In this article, the focus is on the extent to which in biblical texts violence is deemed acceptable in punishing adultery. Jesus’ attitude to this severe punishment is discussed. Jesus concurs with the sanction imposed by Moses but the effect of his requirement that each individual in the group of executioners be without sin, is in fact that the punishment cannot be carried out. The way in which Jesus intervenes is in line of discussions in the Old Testament and in early Judaism that are aimed at imposing restraints of the use of violence in punishing sexual offences. The article concludes with an evaluation of the topical relevance or irrelevance of the two biblical pasages discussed here.